THE IMPACT OF JOB SATISFACTION AND EMPLOYEE ENGAGEMENT ON ORGANIZATIONAL COMMITMENT - Sutiyem Sutiyem; Dessy Trismiyanti; Muthia Roza Linda; Riza Yonita; Suheri Suheri (Dinasti Publisher, 2020)
This study aimed to analyze the influence organization comitment, Job Satisfaction and Employee Engagement. The research was conducted by taking samples of banking employees who had worked for more than 2 years. Then, the sample of this study was 125 respondents. The sampling technique was carried out based on a non-probability sampling method with a purposive sampling technique. It is a method that is based on certain criteria met by respondents with the data analysis technique used for hypotheses testing was multiple linear regression analysis through the program of SPSS ver. 24. The results showed that Job satisfaction does not significantly influence the organizational commitment of banking employees in Padang. The results of this study showed that sig. value of job satisfaction on organizational commitment was 0.592 > 0.05 but Employee engagement has a positive and significant effect on the organizational commitment of banking employees in Padang. The results of this study revealed that sig. The value of employee engagement on organizational commitment was 0.000 < 0.05.